Strategi Harga Bakso Malang Saat Kenaikan Bahan Baku di Lingkungan Kampus UPB - Nabilah Dwi Ananda; Nisa Azzahra; Pupung Purnamasari (GLOBAL SCIENTS PUBLISHER, 2025)
This study aims to explore the pricing strategies adopted by Bakso Malang vendors around the Universitas Pelita Bangsa (UPB) campus in response to rising production costs. The research employs a descriptive qualitative approach with a case study design, utilizing data collection techniques such as semi-structured interviews, non-participant observation, and documentation, with data validation through source triangulation. The findings reveal that the vendors implement three primary strategies: (1) cost-based pricing to ensure production costs are covered, (2) price adjustment through portion or quality reduction (downsizing), and (3) value-based pricing that reflects consumer perception of product worth. These findings offer significant contributions to the literature on micro and small enterprise (MSE) pricing strategies by highlighting the socio-cultural and psychological dimensions often overlooked in quantitative approaches. The practical implications emphasize the need for context-sensitive pricing flexibility and the importance of supportive policies that adapt to market dynamics.